Implementasi Sistem Informasi Akuntansi Pembelian Kredit pada PT Athaya Mutiara Gemilang Berbasis Web dan PostgreSQL - Septiani, Yola; Yunanto, Rio (Program Studi D3 Komputerisasi Akuntansi Fakultas Teknik dan Ilmu Komputer , Universitas Komputer Indonesia, 2021)
ABSTRACT This practical work aims to determine the procedures and internal controls for purchasing goods on credit at PT Athaya Mutiara Gemilang. The practical work will be carried out on October 10, 2021 until November 12, 2021. The basic methods used in this practical work are observation, field practice, interviews, and literature study. Meanwhile, the location of practical work is taken intentionally. PT Athaya Mutiara Gemilang was chosen because the company is a company engaged in the procurement of goods and services, especially when the purchase of goods is made on credit. After doing practical work, it is known that the company always makes credit purchases for the goods needed. The process of recording credit purchase transactions and repayment of credit purchases is still carried out through paid websites and requires substantial funds. Therefore, tools are needed to make reporting easier, automatic, effective, and efficient. This web-based application can make it easier to record transactions and make reports, especially those related to purchasing credit for goods and make it easier to make supplier and vendor selection decisions before making credit purchases of goods.